Socialization of the Bad Effects of Smoking on Youth in Mountainous Areas, India - Dineshne Dineshne (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
The purpose of this research was to examine how well group outings can teach young people in hilly regions about the hazards of tobacco use. The research project included a wide range of educational events, such as seminars, workshops, and awareness campaigns, all aimed at spreading the word about the dangers of smoking. Fifty teenagers (15-24) from the mountains participated in this study. Knowledge and perspective about smoking were assessed by giving participants pre- and post-tests. The outcomes indicated that participants gained substantial knowledge and exhibited a positive attitude shift regarding smoking. Findings from the study point to the potential importance of socialization activities in reducing adolescent smoking in mountainous regions. As a result, it is suggested that similar campaigns be maintained in order to educate the younger generation on the dangers of smoking and encourage them to adopt better lifestyles.